(untitled) (Journal of Computational Mathematics, 1999)
For the sparse linear equations Kx=b, where K arising from optimization and discretization of some PDEs is symmetric and indefinite, it is shown that the L L^T factorization can be used to provide an "exact" preconditioner for SYMMLQ and UZAWA algorithms. "Inexact" preconditioner derived from approximate factorization is used in the numerical experiments.